BALANCING SUSTAINABILITY AND INNOVATION: EXPLORING THE INTERVENTION OF STRATEGIC AMBIDEXTERITY IN PROCESS INNOVATION - Muhammad, Mukarram; Muhammad Haseeb, Shakil; Sadaf, Ehsan; Rao Tahir, Anees; Nordiana, Ahmad Nordin (UNIMAS Publisher, 2025)
Accomplishing sustainable performance notwithstanding an inexorably uncertain environment has become both a basic test and a convincing objective inside the domain of contemporary business. Even with rising uncertainty, accomplishing sustainable performance has arisen as a foremost test and a convincing objective in contemporary business. The study aims to address the imperative set by the United Nations Sustainable Development Goals (UN-SDGs) by exploring the mediation role of strategic ambidexterity in the relationship between intellectual capital dimensions (Structural Capital, Relational Capital, Human Capital, Social Capital) and sustainable performance within businesses. Given the increasing global challenges, particularly the call for sustainability, this research investigates the intricate connections among these variables. Employing quantitative methods and Smart PLS, the study conducted an online survey distributed to managers of selected hotels, yielding 385 workable responses out of 500. The results reveal a positive correlation among the variables of interest, confirming the acceptance of all hypotheses. In conclusion, the findings suggest that hotels strategically leveraging their intellectual capital for innovative exploration and exploitation processes exhibit enhanced capabilities to attain sustainable performance, aligning with the broader goals of global sustainability. The managers could benefit from the implementation of putting resources into the turn of maintenance of a very capable workforce, supporting social ties inside and outside the association. Furthermore, executing situation arranging and possibility techniques empower fast arrangement, adding to sustained performance.